Production flow improvement in a textile industry - Lopes, Jose J. (2018)
Enhance production flow in a Company is of prior importance, not just regarding the general functioning of the underlying production system itself but also regarding all the more or less closely related issues, varying from the warehouse organization and materials handling and space management, to general productivity improvements to reach by a Company. In this paper is presented a case study regarding the analysis of production flow in a textile company in Portugal, and the main improvements proposals are exposed and briefly described.